Implementasi E-Commerce Sebagai Upaya Untuk Meningkatkan Pemasaran Produk di Ud Bintang ABC di Karangrejo Purwosari - Nur Rohmat Nuzil; Dini Ubaidillah; Muhammad Fu’ad (PT. Adriani Mandiri Publisher, 2026)
UD Bintang ABC is one of the UMKM tile bags operating in Karangrejo village Pasuruan Regency. This UMKM was founded 20 years ago by mr. H. Wanali, but has not developed rapidly because of problems in the marketing sector. In the advanced era and the level of tighter business competition, this UMKM still applies traditional marketing as its main form of marketing, because of the lack of knowledge about digital marketing. This service program is done with a direct accompaniment to how to apply digital marketing. The market place offered to the business owner is the marketplace of shopee. Service teams are directly associated with registration, operation, until the way to upload the product at marketplace of shopee. The method used in this service program is the PAR method. With these development and accompanying programmes, it is expected that the UMKM can develop in its marketing sector.